The Impact Of Sovereign Credit Ratings on Foreign Direct Investment and Economic Growth in Egypt - Sanad, Shereen Atef Mahmoud; Elfiky, Fakhry El Din Ali; Salem , Yasmine Mohieeldin Gharieb (Journal of Ecohumanism, 2025)
The purpose of this study is to investigate the strength of the relationship between Sovereign Credit Ratings (SCR) and Foreign Direct Investment (FDI) and Economic Growth, by analyzing how changes in SCRs overtime have influenced investors’ decisions to invest in Egypt. This study employs annual time-series data spanning from 1996 to 2023 to investigate the influence of Sovereign Credit Ratings (SCRs) on Foreign Direct Investment (FDI) and Economic Growth in Egypt. The Autoregressive Distributed Lag (ARDL) approach is utilized to ascertain both the short-run and long-run relationships among these variables. The empirical study reveals a robust correlation between Sovereign Credit Ratings (SCRs), Foreign Direct Investment (FDI), and Economic Growth in Egypt. Moreover, the analysis indicates that SCRs exert a more significant influence on Foreign Direct Investment compared to their impact on Economic Growth. This research underscores the critical role of Sovereign Credit Ratings (SCRs) in attracting foreign direct investment (FDI) and fostering economic growth in Egypt. Policymakers should prioritize initiatives to enhance the country’s business climate, thereby improving its creditworthiness and attracting investors. By implementing these measures, Egypt can create a more favorable environment for economic development and prosperity.